Pyrolysis of waste tyres – The effect of reaction kinetics on the results of thermogravimetric analysis - Cherbański Robert; Wróblewski Krzysztof; Molga Eugeniusz (Chemical and Process Engineering)
This paper presents a systematic thermogravimetric (TG) study on the kinetics of end-of-life tyre (ELT) pyrolysis. In the experimental part of this work, TG results are compared for tyre samples of different mass and size. This shows that the conduction resistance in the milligram scale (up to ~100 mg) tyre sample can be neglected. A comparison of experimental results demonstrates that the characteristic maxima on the DTG curve (the first derivative of TG signal) shift towards higher temperatures for higher heating rates. This phenomenon is explained to have kinetic origin and it is not caused by the internal heat transfer resistance. In the modelling part of this work, the kinetic parameters of the Three-Component Simulation Model (TCSM) are calculated and compared to the literature values. Testing of the kinetic model is carried out using experiments with a varying heating rate. This shows the limitation of the simplified kinetic approach and the appropriate selection method of the kinetic parameters.